Modulation of the anatomical and physiological responses of in vitro grown Alcantarea imperialis induced by NAA and residual effects of BAP - Martins, João Paulo Rodrigues; Rodrigues, Luiz Carlos de Almeida; Silva, Thayna dos Santos; Gontijo, Andreia Barcelos Passos Lima; Falqueto, Antelmo Ralph (Ornamental Horticulture, 2020)
During in vitro propagation, cytokinins (CKs) and auxins (AUXs), such as 6-benzylaminopurine (BAP) and 1-naphthaleneacetic acid (NAA), are often used to induce adventitious shoots and roots, respectively. However, it is not clear how CKs affect plants over a long period of in vitro propagation as well as the synergy of direct exposure to AUX with previous CK treatments. The aim was to assess the physiological and anatomical responses of Alcantarea imperialis in function of the interaction of both previous BAP treatments and direct NAA exposure during in vitro propagation. Plants previously grown in vitro were transferred to media containing 0, 5, 10 or 15 μM BAP. After 60 days, the adventitious shoots from each previous BAP treatment were subcultured in media with 0, 2 or 4 μM NAA. Pigment content, anatomical and growth traits were assessed in the plants from each treatment. Both previous BAP treatments and direct NAA exposure altered the anatomy and pigment contents of plants as well as their growth traits. BAP induced negative effects over the long term on physiological status as well as changed the plants’ anatomy. NAA supplementation in the medium can partially reverse the negative effects induced by BAP. The application of 2 μM NAA during in vitro rooting improved the plants’ quality